2024
DOI: 10.3390/infrastructures9050087
|View full text |Cite
|
Sign up to set email alerts
|

Traffic Flow Optimization at Toll Plaza Using Proactive Deep Learning Strategies

Habib Talha Hashmi,
Sameer Ud-Din,
Muhammad Asif Khan
et al.

Abstract: Global urbanization and increasing traffic volume have intensified traffic congestion throughout transportation infrastructure, particularly at toll plazas, highlighting the critical need to implement proactive transportation infrastructure solutions. Traditional toll plaza management approaches, often relying on manual interventions, suffer from inefficiencies that fail to adapt to dynamic traffic flow and are unable to produce preemptive control strategies, resulting in prolonged queues, extended travel time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Bertini et al used computerized microscopic traffic simulation programs Paramics and VISSIM to analyze a diamond interchange in Portland, Oregon [41]. Simulation models allow designers to analyze non-existing situations, like adding a new lane or turn bay and studying the impact of geometric changes, or optimizing traffic flow at toll plaza [42,43]. Mosseri et al studied a multi-modal urban corridor with complex geometry and traffic control in VISSIM [44].…”
Section: Microsimulation Of Traffic Congestionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bertini et al used computerized microscopic traffic simulation programs Paramics and VISSIM to analyze a diamond interchange in Portland, Oregon [41]. Simulation models allow designers to analyze non-existing situations, like adding a new lane or turn bay and studying the impact of geometric changes, or optimizing traffic flow at toll plaza [42,43]. Mosseri et al studied a multi-modal urban corridor with complex geometry and traffic control in VISSIM [44].…”
Section: Microsimulation Of Traffic Congestionmentioning
confidence: 99%
“…Hashmi et al optimized the traffic flow at toll plaza using neural network models and VISSIM v7 for a case study of Ravi toll plaza in Lahore. The simulation results showed that fuel consumption costs, vehicle delays, and pollutant emissions were reduced by 28.4%, 47%, and 34%, respectively by optimizing the traffic flow [43]. Karthik and Loui developed a congestion model for Kerala, India, which estimated the congestion cost to be almost 25% of the total expenditure on road infrastructure in the 2021 budget [52].…”
Section: Quantification Of Urban Traffic Congestionmentioning
confidence: 99%